2000
DOI: 10.1097/00003246-200008000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of quantitative invasive diagnostic techniques in the management and outcome of mechanically ventilated patients with suspected pneumonia

Abstract: In our study population, the routine use of quantitative invasive diagnostic tools is not justified in the setting of ventilated patients clinically suspected of having nosocomial pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(93 citation statements)
references
References 17 publications
0
86
0
7
Order By: Relevance
“…In the three, randomized, controlled Spanish studies, no differences in mortality and morbidity were found when either invasive (PSB and/or BAL) or QEA techniques were used to diagnose VAP (175,176,186). However, these studies contained relatively few patients (51, 76, and 88 patients) and therefore were not powered sufficiently to demonstrate a difference in mortality.…”
Section: Microbiologic Diagnosismentioning
confidence: 97%
“…In the three, randomized, controlled Spanish studies, no differences in mortality and morbidity were found when either invasive (PSB and/or BAL) or QEA techniques were used to diagnose VAP (175,176,186). However, these studies contained relatively few patients (51, 76, and 88 patients) and therefore were not powered sufficiently to demonstrate a difference in mortality.…”
Section: Microbiologic Diagnosismentioning
confidence: 97%
“…Basically, the following conclusions appear evident: 1) the diagnostic value of the quantitative culture from endotracheal aspirate is similar to that provided by invasive methods (protected specimen brush, bronchoalveolar lavage) [23,87]; 2) the invasive techniques lead to more changes of the antibiotic treatment but without any improvement of mortality and morbidity rate [22,23,85]; and 3) the endotracheal aspirate is less expensive compared to the invasive investigation [23,88]. However, further studies are required to establish which is the best approach for the diagnosis of ventilator-associated pneumonia, since the experts9 opinions are still divided.…”
Section: Invasive Versus Noninvasive Techniques For Diagnosing Ventilmentioning
confidence: 89%
“…There are only three studies complying with these criteria [22,23,85]. SANCHEZ-NIETO et al [22] reported that bronchoscopy led to more frequent antibiotic changes and a greater cost of antibiotic therapy, with no change in morbidity and mortality rate.…”
Section: Invasive Versus Noninvasive Techniques For Diagnosing Ventilmentioning
confidence: 99%
See 1 more Smart Citation
“…This has paved the way for less invasive tests such as endotracheal aspirates (ETA) and quantitative ETA cultures with a threshold of 10 5 to 10 6 bacteria per milliliter of exudates that is considered as optimal for the microbiological conÞ rmation of VAP. [3] More importantly, recent small trials have repeatedly shown that there is no advantage of bronchoscopic cultures over quantitative ETA cultures when mortality was considered as the end-point, [4][5][6] further strengthening the case for quantitative ETA as a diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%